David et Jonathan : christianisme et homophilie. (Paris : G. de Mauve, 1973)
Fonds Suzan Daniel (FSD)
Periodiciteit : ?
Redactie : BP 9107, 75327 Paris Cédex 07
Frans
Periodiek
Keywords: homoseksualiteit; christendom